2014
DOI: 10.1177/0284185113512299
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and types of coronary to pulmonary artery fistula in a Chinese population at dual-source CT coronary angiography

Abstract: Based on this large cohort, the prevalence of CPAF in the Chinese population is about 0.17%, with origin from either the left or right coronary artery or from both. CTCA can clearly visualize the types, abnormal vascular tracts, and aneurysmal sac formation of CPAF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…This discrepancy with cardiac catheterization could have resulted from the difference in the modality used. In our study, 67% of CPAFs originated from both the right and left coronary arteries, which is in accordance with previous studies using CT (53-59%) (16)(17)(18)(19). The remaining 33% of CPAFs in our study originated from a single coronary artery; 25% of CPAFs originated from the LCA and 8% of CPAFs originated from the RCA.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy with cardiac catheterization could have resulted from the difference in the modality used. In our study, 67% of CPAFs originated from both the right and left coronary arteries, which is in accordance with previous studies using CT (53-59%) (16)(17)(18)(19). The remaining 33% of CPAFs in our study originated from a single coronary artery; 25% of CPAFs originated from the LCA and 8% of CPAFs originated from the RCA.…”
Section: Discussionsupporting
confidence: 92%
“…In the recent study done among Chinese population, the prevalence of coronary pulmonary artery fistula (CPAF) was found to be 0.17%, which is thought to be much higher than previously reported in literature [12]. Kim et al [13] reported a 0.32% prevalence of CPAF, based on their finding of 17 CPAF cases in 5372 patients.…”
Section: Epidemiologymentioning
confidence: 88%
“…It is assumed to be due to the fact that the cases detected incidentally during coronary artery evaluation by MDCT were abundant. The possibility for the variation in prevalence among different populations may be due to ethnic differences, and also the retrospective nature of the studies which may miss some small CPAF contribute to the differences in prevalence [12]. Most of the times, literature alludes fistula arising from RCA to be dominant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) Recently, multidetector computed tomography (MDCT) has been used to delineate the complex anatomy of CAF 4) or coronary aneurysm, 5) with recent studies indicating that coronary to pulmonary artery fistulas (CPAFs) are the most common type. [6][7][8] It has been argued that the embryological basis of CPAF is different from other types of CAF, which drain into cardiac chambers, 9,10) and that the resulting left-toright shunt is relatively small through a CPAF. 11) To date, the optimal management for small and asymptomatic CPAFs remains a matter of debate.…”
mentioning
confidence: 99%